USE OF COMPLEX DECONGESTIVE THERAPY WITH LOW COST MATERIAL IN A PATIENT WITH LYMPHEDEMA LIVING IN AN ENDEMIC AREA FOR FILARIASIS - Leonel da Silva, Fernando; Souza Eletherio de Oliveira, Vanessa; Pereira dos Santos Soares, Helen; Soares de Siqueira, Renata; Cristina Santos Cardozo Roque, Letticia; Aguiar-Santos, Maria; Rosângela Grilis de Oliveira, Maria; Brandão, Eduardo; Moutinho Lagos de Melo, Cristiane; Rocha, Abraham; do Amparo Andrade, Maria (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Lymphatic filariasis affects millions of people around the world and may have disabling consequences. Lymphedema stands out as a chronic manifestation in patients with this disease, affecting the lower limbs and limiting motor function. This study aimed to propose a treatment protocol to decrease lower limb lymphedema of treated patients and to show the efficacy of Complex Decongestive Therapy (CDT) as an auxiliary resource for this condition. This is a case study of a patient treated with CDT, making use of compression methods with alternative materials and instructions for asepsis during 10 weeks. The results demonstrated that this treatment reduced lymphedema in the right lower limb of the patient from grade V to grade III, with areas of measurement reduction of up to 41%. In addition, acute dermatolymphangioadenitis (ADLA) manifestations stopped in the treated patient. CDT associated with low-cost compression material, has been shown to be effective in reducing lower limb lymphedema and ADLA crises, as well as in promoting improved locomotion and performance of daily activities by the patient.